ETIKA DAKWAH USTADZ HANAN ATTAKI DALAM CHANNEL YOUTUBE @HANAN ATTAKI - Imulia Rahmadani Aziz (Jurnal Komunikasi, 2023)
In today's era, social media has become one of the platforms for delivering religious teachings to the public. One of the preachers who utilizes social media for this purpose is Ustadz Hanan Attaki. He conducts his preaching through YouTube, where he shares his religious lectures. Ustadz Hanan is a young preacher widely recognized and admired by the youth due to his gentle speaking style and discussions that relate to their everyday lives. This research focuses on the ethical aspects of Ustadz Hanan Attaki's preaching in his video titled "Ustadz Hanan Attaki- Diam" on the YouTube channel @Hanan Attaki. The study employs a qualitative descriptive method to describe and depict the events being studied without data manipulation. Primary data is obtained from Ustadz Hanan Attaki's preaching videos, while secondary data is collected from various books and relevant documents. Data collection is carried out through observation and documentation, with the collected data being processed through data reduction, data presentation, and drawing conclusions. Data validity is ensured through triangulation of time, data sources, and methods to verify the accuracy of the research findings. The research findings from the video "Ustadz Hanan Attaki- Diam" reveal that Ustadz Hanan Attaki demonstrates effective preaching methods. He treats everyone equally, prioritizes sincerity and truthfulness in his messages, and refrains from discussing matters he is not knowledgeable about. Ustadz Hanan also displays patience, respects other religions, and does not impose his opinions. His approach inspires and motivates the younger generation to draw closer to their faith and make positive changes in their lives. His message is conveyed in a friendly and easily understandable manner. Despite his popularity, Ustadz Hanan maintains simplicity in his appearance, aligning with the preferences of the youth